2014
DOI: 10.1007/s00432-014-1658-7
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the effects of beta blocker on survival time in cancer patients

Abstract: This meta-analysis provides evidence that beta blocker use can be associated with the prolonged survival of cancer patients, especially patients with early-stage cancer treated primarily with surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 39 publications
3
46
1
Order By: Relevance
“…The meta‐analysis demonstrated that BB use was associated with prolonged overall survival and disease‐free survival. Further analysis according to cancer type suggested significant effect in breast, ovarian and lung cancer, but not in prostate cancer and melanoma . Our study provides the first clinical evidence demonstrating overall and disease specific survival benefit associated with the use of BB in MM patients.…”
Section: Discussionmentioning
confidence: 61%
“…The meta‐analysis demonstrated that BB use was associated with prolonged overall survival and disease‐free survival. Further analysis according to cancer type suggested significant effect in breast, ovarian and lung cancer, but not in prostate cancer and melanoma . Our study provides the first clinical evidence demonstrating overall and disease specific survival benefit associated with the use of BB in MM patients.…”
Section: Discussionmentioning
confidence: 61%
“…Innervation of the primary tumor has been shown to promote invasiveness, and examination of adrenergic signaling on primary tumor cells and cell lines has demonstrated increased invasiveness and metastatic potential of these cells (39,40). Further, therapy which suppresses beta-adrenergic receptor signaling has been shown to improve relapse free survival, supporting the role of adrenergic signaling in reactivation of dormant tumor cells (41,42). Moreover, Magnon and co-authors (40) completed a series of studies using mice bearing PC3 prostate tumor xenografts that developed tumors and were monitored for metastases.…”
Section: Discussionmentioning
confidence: 87%
“…This was indeed observed in a small number of retrospective studies. 65 b-blockers are safe and well-characterized drugs, used clinically for the treatment of congestive heart failure and high blood pressure. Although these drugs do not seem to affect breast cancer incidence and tumorigenesis, a beneficial effect in terms of less advanced disease at diagnosis and lower cancer-specific mortality was observed in patients who have taken propranolol 1 year before diagnosis.…”
Section: Stress B-blockers and Survival In Patients With Breast Cancermentioning
confidence: 99%